Financial Investment Behavior of Individual Investor in Indonesia After the Revocation of the Covid-19 Policy - Ghazali Syamni; Murhadi, Thasrif; Marzuki, Marzuki; Zainuddin, Zamzami; Yulis Terfiadi, Sari (MATRIK: JURNAL MANAJEMEN, STRATEGI BISNIS, DAN KEWIRAUSAHAAN, 2023)
This study investigates the impact of psychological, social, and demographic aspects on Indonesian individual stock investors' decisions. With the help of Indonesian Stock Exchange Representative Offices in all provinces where there are representatives, this research is based on survey data and involves sending questionnaire links via WhatsApp, telegrams, and emails to participants. Following President Joko Widodo's announcement that social restrictions imposed during the previous pandemic had been lifted, the spread began after an initial one-week period in the first week of 2023. Thus, 108 questionnaire responses were collected for the survey. The findings demonstrated that individual stock investors' behavior was unaffected by gender, age, or marital status. Work, education, and experience have a positive and considerable influence on individual investors' investment behavior; however, the removal of social restraints has a negative impact on this behavior. According to the study's findings, education degree is the main variable that significantly affects stock investors' behavior.